2006
DOI: 10.1007/s10948-006-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Current Imaging in Passive HTS Components by Low-Temperature Laser Scanning Microscopy (LTLSM)

Abstract: distributed parameters in SC films as a function of the local critical current [27]. It is possible to manifest local resistive characterization of the SC transition [28][29][30], the spatial variations of magnetic and electromagnetic fields [31][32][33][34], and to carry out 2-D defectoscopy of structural and technological faults in operating SC devices and circuits [35][36][37]. In this work, we apply the LTLSM technique to analyze the redistribution of rf current flow in the vicinity of typical microdefects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(42 reference statements)
0
15
1
Order By: Relevance
“…A dc magnetic field was shown to add magnetic flux to a thin-film Nb SRR, increasing its inductance and loss [40]. The rf magnetic field created enhanced rf screening currents at discrete locations in the SRR, resulting in enhanced inductance and dissipation as magnetic flux moved into and out of the superconducting film at high frequency [40,[42][43][44][45][46]. It was also found that a superconducting resonator exhibiting an analogue of electromagnetically induced transparency showed a strong switching behavior at high excitation power [36], for similar reasons.…”
Section: A Tunable Superconducting Metamaterialsmentioning
confidence: 99%
“…A dc magnetic field was shown to add magnetic flux to a thin-film Nb SRR, increasing its inductance and loss [40]. The rf magnetic field created enhanced rf screening currents at discrete locations in the SRR, resulting in enhanced inductance and dissipation as magnetic flux moved into and out of the superconducting film at high frequency [40,[42][43][44][45][46]. It was also found that a superconducting resonator exhibiting an analogue of electromagnetically induced transparency showed a strong switching behavior at high excitation power [36], for similar reasons.…”
Section: A Tunable Superconducting Metamaterialsmentioning
confidence: 99%
“…The power of the laser P L =10μW was fixed low enough to introduce minimal perturbation on the global microwave properties of the resonator. The intensity of the laser is modulated at a frequency of f M =100 kHz, producing an oscillating thermal probe of about 4 μm in diameter [3,4,6,7]. Transmitted HF signals are amplified and measured by a spectrum analyzer, as shown in Fig.2.…”
Section: B Imaging Proceduresmentioning
confidence: 99%
“…Alexander P. We have shown earlier that the low-temperature Laser Scanning Microscope (LSM) is a powerful nondestructive evaluation technique for non-contact, spatially-resolved probing of the local HF current density, J HF (x,y) in HTS films and devices [3]. This LSM method was applied next for mapping optical, thermal, HF and dc electron transport properties and superconducting critical parameters of HTS samples directly in their operating state at T < T c , with micronscale spatial resolution [4].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the LSM photoresponse is a linear function of laser power up to ∼ 100 µW of absorbed laser power when the critical state of the Josephson junction is achieved by overheating by laser. Temperature modulation estimates for LSM measurements have been published before in references [52][53][54][55]…”
Section: S2 Lsm Techniquementioning
confidence: 99%